Faktor yang Mempengaruhi Minat Keluarga dalam Memilih Pelayanan Home Care pada Bayi - Lili Purnama Sari; Arisna Kadir; Irnawati Irnawati; Uliarta Marbun; Dahniar Dahniar (Jurnal Sehat Mandiri, 2024)
Along with the rapid development of improvements in the level of public health, the concept of health services has changed, previously people visiting health services have begun to change and develop into home care. Home health services or Home care is a component of comprehensive health services where health services are provided to individuals and families where they live. This study aims to determine the factors that influence family interest in choosing home care services for babies. The majority of babies who visit choose home care services at TPMB Irma Dewi. This type of research is quantitative research using a cross sectional study design. This research was carried out at TPMB Irma Dewi from May to July 2023. The sample collection technique was non-probability sampling using Accidental Sampling, the sample size was 35 people. The sample in this study were babies who used home care services at TPMB Irma Dewi. Based on the research results, the value of p = 0.028 was obtained, which means it is smaller than α (0.05). It can be concluded that family support can be a factor that influences family interest in choosing home care services for babies at TPMB Irma Dewi. So it is recommended that families choose quality home care in health services for babies.